Pharmacokinetics and subjective effects of a novel oral LSD formulation in healthy subjects - Holze, Friederike (Br J Clin Pharmacol, 2019)
AIMS: The aim of the present study was to characterize the pharmacokinetics and exposure–subjective response relationship of a novel oral solution of lysergic acid diethylamide (LSD) that was developed for clinical use in research and patients. METHOD: LSD (100 μg) was administered in 27 healthy subjects using a placebo‐controlled, double‐blind, cross‐over design. Plasma levels of LSD, nor‐LSD, and 2‐oxo‐3‐hydroxy‐LSD (O‐H‐LSD) and subjective drug effects were assessed up to 11.5 hours. RESULTS: First‐order elimination kinetics were observed for LSD. Geometric mean maximum concentration (C (max)) values (range) of 1.7 (1.0–2.9) ng/mL were reached at a t (max) (range) of 1.7 (1.0–3.4) hours after drug administration. The plasma half‐life (t (1/2)) was 3.6 (2.4–7.3) hours. The AUC(∞) was 13 (7.1–28) ng·h/mL. No differences in these pharmacokinetic parameters were found between male and female subjects. Plasma O‐H‐LSD but not nor‐LSD (< 0.01 ng/mL) concentrations could be quantified in all subjects. Geometric mean O‐H‐LSD C (max) values (range) of 0.11 (0.07–0.19) ng/mL were reached at a t (max) (range) of 5 (3.2–8) hours. The t (1/2) and AUC(∞) values of O‐H‐LSD were 5.2 (2.6–21) hours and 1.7 (0.85–4.3) ng·h/mL, respectively. The subjective effects of LSD lasted (mean ± SD) for 8.5 ± 2.0 hours (range: 5.3–12.8 h), and peak effects were reached 2.5 ± 0.6 hours (range 1.6–4.3 h) after drug administration. EC(50) values were 1.0 ± 0.5 ng/mL and 1.9 ± 1.0 ng/mL for “good” and “bad” subjective drug effects, respectively. CONCLUSION: The present study characterized the pharmacokinetics of LSD and its main metabolite O‐H‐LSD. The subjective effects of LSD were closely associated with changes in plasma concentrations over time.